2007
DOI: 10.1063/1.2730503
|View full text |Cite
|
Sign up to set email alerts
|

Direct-drive laser target designs for sub-megajoule energies

Abstract: New direct-drive laser target designs with KrF laser light take advantage of the shorter wavelength to lower the laser energy required for substantial gain (>30x) to sub-MJ level. These low laser-energy pellets are useful in systems that could form an intermediate step towards fusion energy, such as the proposed Fusion Test Facility [S. P. Obenschain,et al, Phys. Plasmas 13, 056320 (2006)]. The short wavelength laser should allow higher intensity (and higher pressure) without increasing the risk of laser-plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Details of the ongoing development of sub-MJ implosion designs with KrF lasers are discussed in another paper. 7 Application of high intensity laser pulses to direct and indirect drive implosions is limited by the occurrence of LPI in the underdense plasma surrounding the pellet. 9 Deep ultraviolet (248 nm) KrF lasers will help mitigate the risk from LPI.…”
Section: Introductionmentioning
confidence: 99%
“…Details of the ongoing development of sub-MJ implosion designs with KrF lasers are discussed in another paper. 7 Application of high intensity laser pulses to direct and indirect drive implosions is limited by the occurrence of LPI in the underdense plasma surrounding the pellet. 9 Deep ultraviolet (248 nm) KrF lasers will help mitigate the risk from LPI.…”
Section: Introductionmentioning
confidence: 99%
“…The facility design incorporated and extended the HAPL database but required a target design energy scaled down from the original 2.5 MJ to the anticipated 500-kJ KrF laser. Colombant et al 871 accomplished this, predicting 1-D target gains of just over 50. Other attractive features of the FTF include the implementation and testing of 5-Hz implosion operation and the application of functional focal-spot zooming. In support of the proposed FTF, Kehne et al 872 at NRL demonstrated focal-spot zooming by a margin (4.5:1) that exceeds what would be required by the FTF.…”
Section: Ignition and High-gain Target Designsmentioning
confidence: 97%
“…13 is NRL's original calculation [65] of what is called central ignition. The same laser pulse is used to both compress the inner part of the target and to heat it.…”
Section: Direct Drivementioning
confidence: 99%